1998
DOI: 10.1029/97gl03776
|View full text |Cite
|
Sign up to set email alerts
|

Melting and crystal structure of iron at high pressures and temperatures

Abstract: Abstract. High-pressure melting, phase transitions and structures of iron have been studied to 84 GPa and 3500 K with an improved laser heated diamond anvil cell technique and in situ high P-T x-ray diffraction. At pressures below 60 GPa, the lower bound on the melting curve is close to those measured by Boehler [1993] and Saxena et al. [1993]; however, at pressures above 60 GPa our data indicate melting at higher temperatures than these studies, but still lower than the melting curve of Williams et al [1990]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
230
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(265 citation statements)
references
References 19 publications
31
230
4
Order By: Relevance
“…Other experimentalists, however, have failed to detect such a post-hcp phase (e.g. Shen et al, 1998;Nguyen and Holmes, 2004), and have suggested that the previous observations were due either to minor impurities or to metastable strain-induced behaviour. Figure 1 also shows that there is also considerable disagreement between different theoretical studies.…”
Section: Introductionmentioning
confidence: 92%
“…Other experimentalists, however, have failed to detect such a post-hcp phase (e.g. Shen et al, 1998;Nguyen and Holmes, 2004), and have suggested that the previous observations were due either to minor impurities or to metastable strain-induced behaviour. Figure 1 also shows that there is also considerable disagreement between different theoretical studies.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, we know from other experiments on iron [14] that when iron is quenched from the stability field of the fcc phase, the XRD pattern of the quenched sample shows lines belonging to hcp and double hcp phases. Therefore, it is not necessary that the fcc peaks in XRD patterns of quenched samples are due to the stabilization of the fcc phase at high temperature.…”
mentioning
confidence: 93%
“…This EAM has been proved to perform very well. For example, it allows one to reproduce the structure of liquid iron [14]- [16] as well as its viscosity [7,17]. It also allows one to explain a number of features of IC [9,10].…”
mentioning
confidence: 99%
“…3). This melting criterion has been applied in many previous investigations to determine melting in a wide variety of substances [20][21][22] and it has been directly correlated with the appearance of liquid S(Q) during in situ x-ray diffraction experiments in the LH-DAC [14,20].…”
Section: B Thermal Signal Processingmentioning
confidence: 99%